Correlation between Ferumoxytol Uptake in Tumor Lesions by MRI and Response to Nanoliposomal Irinotecan in Patients with Advanced Solid Tumors: A Pilot Study - Ramanathan, Ramesh K.; Korn, Ronald L.; Raghunand, Natarajan; Sachdev, Jasgit C.; Newbold, Ronald G.; Jameson, Gayle; Fetterly, Gerald J.; Prey, Joshua; Klinz, Stephan G.; Kim, Jaeyeon; Cain, Jason; Hendriks, Bart S.; et al. (Clinical cancer research, 2017)
Purpose: To determine whether deposition characteristics of ferumoxytol (FMX) iron nanoparticles in tumors, identified by quantitative MRI, may predict tumor lesion response to nanoliposomal irinotecan (nal-IRI). Experimental Design: Eligible patients with previously treated solid tumors had FMX-MRI scans before and following (1, 24, and 72 hours) FMX injection. After MRI acquisition, R2* signal was used to calculate FMX levels in plasma, reference tissue, and tumor lesions by comparison with a phantom-based standard curve. Patients then received nal-IRI (70 mg/m2 free base strength) biweekly until progression. Two percutaneous core biopsies were collected from selected tumor lesions 72 hours after FMX or nal-IRI. Results: Iron particle levels were quantified by FMX-MRI in plasma, reference tissues, and tumor lesions in 13 of 15 eligible patients. On the basis of a mechanistic pharmacokinetic model, tissue permeability to FMX correlated with early FMX-MRI signals at 1 and 24 hours, while FMX tissue binding contributed at 72 hours. Higher FMX levels (ranked relative to median value of multiple evaluable lesions from 9 patients) were significantly associated with reduction in lesion size by RECIST v1.1 at early time points (P < 0.001 at 1 hour and P < 0.003 at 24 hours FMX-MRI, one-way ANOVA). No association was observed with post-FMX levels at 72 hours. Irinotecan drug levels in lesions correlated with patient's time on treatment (Spearman ρ = 0.7824; P = 0.0016). Conclusions: Correlation between FMX levels in tumor lesions and nal-IRI activity suggests that lesion permeability to FMX and subsequent tumor uptake may be a useful noninvasive and predictive biomarker for nal-IRI response in patients with solid tumors. Clin Cancer Res; 23(14); 3638–48. ©2017 AACR.